Using Zinc in Management of Subfertile Male Patients: a Clinical Trial - Saeed, Husamuldeen Salim Mohammed (AL-Kindy College Medical Journal, 2019)
Background: The use of minerals in treatment of different diseases is as old as man himself. zinc is the most famous trace mineral related to male sexual function. Oligoasthenozoospermic subfertile patients were treated with zinc sulphate for three months. Objectives: Aim of the research is to investigate the role of Zinc and if it affects the abnormalities of some semen parameters and to study the possible role of pharmaceutical preperations of zinc in amelioration of male subfertility as well as to assess the ability of Zinc to induce changes in the serum and semen zinc levels in addition to the levels of reproductive hormones (FSH and Testosterone). Type of the study: The study is a single group pretest-posttest experimental prospective comparative self-control; clinical trial research. Methods: The patients were tested before and after the treatment for semen analysis via Computerized Assisted Semen Analysis (CASA) dynamic analysis report I and II as well as for FSH and Testosterone hormonal levels, serum and semen zinc levels . Results: Zinc administration induced a significant increase(p≤0.001) in FSH, Testosterone, serum and semen zinc level as well as in the total and progressive sperm motility percentages . Conclusions: Zinc administration induced significant changes (p≤0.001) towards improvement in the total and progressive sperm motility percentages in oligoasthenozoospermic patients by CASA dynamic analysis report I and II.